SPRINGATE SCORE ANALYSIS IN PREDICTING FINANCIAL DISTRESS IN ISLAMIC BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Bulan, Sri; Rismala; Hamid, Abdul (Institut Agama Islam Negeri Parepare, 2025)
Springate score analysis is an analysis that can help companies to anticipate the possibility of a company going bankrupt caused by a company's financial problems. This study aims to find out and analyze the potential for financial distress in Islamic banking companies listed on the Indoensai Stock Exchange (IDX) for the 2019-2023 period using a springate score. The data source used in this study comes from financial statements in the form of the company's balance sheet and profit and loss obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The type of research used is descriptive research with a quantitative approach. This study uses a data analysis technique in the form of a springate score calculation which combines four financial ratios, namely working capital to total assets, earning before interest and taxed to total assets, earning before tax to current liabilities and sales to total assets. The assessment category of companies that are in the healthy zone (non-financial distress > 1.062), vulnerable zone (grey zone > 0.862 S < 1.062) and experiencing bankruptcy risk (financial distress < 0.862). The results of the research obtained are that Bank Tabungan Pensiunan Nasional Syariah Tbk is in a healthy condition or non-financial distress from 2019-2023. PT. Bank Aladin Syariah Tbk is in the financial distress category in 2020-2023. PT. Bank Syariah Indonesia was in a state of financial distress in 2019-2020. And PT. Bank Panin Dubai Syariah is in a state of financial distress in 2021 and 2023.